2018
DOI: 10.1016/j.isci.2018.01.003
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional Co-activator Functions of YAP and TAZ Are Inversely Regulated by Tyrosine Phosphorylation Status of Parafibromin

Abstract: SummaryYAP and TAZ, the Hippo signal-regulated transcriptional co-activators, play crucial roles in morphogenesis and organogenesis. Here we report that the YAP/TAZ activities are stimulated upon complex formation with Parafibromin, which undergoes tyrosine phosphorylation and dephosphorylation by kinases such as PTK6 and phosphatases such as SHP2, respectively. Furthermore, TAZ and the Wnt effector β-catenin interact cooperatively with tyrosine-dephosphorylated Parafibromin, which synergistically stimulates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…First, increased cytoplasmic TAZ may bind to β-catenin and/or disheveled in the cytoplasm to hinder β-catenin's nuclear translocation consistent with previous studies. 38 , 39 Alternatively, increased cytoplasmic TAZ may negatively regulate expression/activity of YAP in the nucleus in agreement with a previous study from our group in corneal stromal cells, 86 and that of Tang and colleagues, 87 who demonstrated that the transcriptional co-activator functions of YAP and TAZ are inversely regulated by tyrosine phosphorylation status of parafibromin. It is also likely that 10% XCDM-induced cell stiffening may be independent of the conventional mechanotransduction signaling axis of YAP/TAZ, which typically involves ROCK or actomyosin activity.…”
Section: Discussionsupporting
confidence: 89%
“…First, increased cytoplasmic TAZ may bind to β-catenin and/or disheveled in the cytoplasm to hinder β-catenin's nuclear translocation consistent with previous studies. 38 , 39 Alternatively, increased cytoplasmic TAZ may negatively regulate expression/activity of YAP in the nucleus in agreement with a previous study from our group in corneal stromal cells, 86 and that of Tang and colleagues, 87 who demonstrated that the transcriptional co-activator functions of YAP and TAZ are inversely regulated by tyrosine phosphorylation status of parafibromin. It is also likely that 10% XCDM-induced cell stiffening may be independent of the conventional mechanotransduction signaling axis of YAP/TAZ, which typically involves ROCK or actomyosin activity.…”
Section: Discussionsupporting
confidence: 89%
“…Exclusive to YAP are an N-terminal proline-rich domain interacting with tight junction protein 1 (TJP1) [108] and a central SH3 domain. Although the binding partners of the YAP SH3 domain are largely elusive, it may be responsible for the exclusive interaction of YAP with nuclear tyrosine-phosphorylated parafibromin (CDC73), while TAZ selectively binds to unphosphorylated parafibromin in complex with β-catenin [109]. In addition to acting as a transcriptional co-activator, there is evidence that TAZ plays a role in protein degradation through interaction with the E3 ligase BTRC [110].…”
Section: Yap and Taz-functionally Redundant?mentioning
confidence: 99%
“…However, Taz conventional knockout mice only exhibit some developmental defects such as polycystic kidney and emphysema [46-48]. In addition, Yap and Taz exert different biological functions in myogenic differentiation and they are differently regulated through distinct interaction with Parafibromin [49, 50]. Not surprisingly, we indeed found that the expression level of Taz in mouse lens was much lower than Yap.…”
Section: Methodsmentioning
confidence: 82%